(untitled) (Global Journal of Science Frontier Research, 2019)
Recent study found that the ratio of oxygen isotopes the Earth and the Moon. Study of Martian rocks also showed that Mars does not have field. Since the ring currents, which the planetary magnetic field of each planet, the lack of liquid magma. Indeed, the lack of volcanic surface mean exactly this. Why is Mars an old and cold planet, while system have hot liquid magma? Also, as far back as in 1619 Kepler wrote in his book Mundi that the ratio of diverging and converging ratio 18:19 in our Solar System. Maybe, we should believe the claims that the planet Mars was sucked into our when the last was merging through it. We can still see in our telescopes Dwarf Galaxy with the remaining stars Dwarf Galaxy consists of old (dwarf) stars that barely shine Mars was found to be an old and cold planet, it was probably sucked from the old Dwarf as the ancient Hindu texts said.